Políticas de formação inicial docente no Brasil: novas versões, antigas concepções (Olhar de Professor, 2023)
With this article, I aim to discuss issues related to the initial training of teachers in undergraduate courses, with regard to the knowledge of teaching practice, curriculum, didactics, legal provisions and the orientation of the reformulation of pedagogical projects of the courses of degrees, with emphasis on the Common National Base for the Initial and Continuing Training of Basic Education Teachers (better known as BNC-Training), approved on December 20, 2019. This is a literature review, based on the analysis of guiding documents for the training of teaching professionals, as well as authors and researchers who discuss initial training, as well as the theoretical-practical tensions that permeate this training. We consider, based on the documents analyzed and based on researchers from Anfope and Anped who repudiated the BNC-Formação, that the proposal is reductionist in terms of teaching work and that it goes back in the understanding of the inseparability between theory and practice, a discussion already well established in the educational field.
Keywords: BNC-Training. Initial teacher training. Curriculum reformulation.